SOCIAL NETWORK AND LAND CONFLICT IN RURAL COMMUNITIES (CASE STUDY IN SENAMA NENEK VILAGE TAPUNG HULU SUB REGENCY KAMPAR REGENCY) - HERLON, MEKI; RESTUHADI, FAJAR; YULIDA, ROZA (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2017)
One of the government effort in accelerated development is believed to be done with maximum natural resource management, sustainable, and without any conflict. This 2800 ha of land conflict happened between rural citizen in sub regency Tapung Hulu and PTPN V Kebun Sei Kencana. The aim of this research is to find out information about social network and land conflict in rural communities in Senama Nenek vilage. This research is done within November 2015 until March 2016. Research method is using survey method and research sample for community leaders (12 people by census) and ordinary citizen (113 people by Snow Ball). The data that needed is primary and secondary data, the analysis used SPSS and UciNet program. The result showed that there are 12 actors involved in this conflict which are : 8 actors that maintain customary land (Ishk, Myya, Mkwr, Frds, Abms, Ahyn, dan Tmsn) and 4 actors uphold interests of the company (Abcn, Sprn, Sjls, dan Srdi).